Konsep Dasar Proses Pembuatan Membran Berpori dengan Metode Non-Solvent Induced Phase Separation - Penentuan cloud point dan diagram tiga phasa - Nasrul Arahman (Jurnal Rekayasa Kimia & Lingkungan, 2012)
Application of membrane technology for separation processes has been an efficient optional to produce a high quality of separation product. This process has been widely using in many field of industry. Therefore, knowledge of this membrane preparation is important for controlling the pore size of resulted membrane. This paper explained the basic concept of membrane preparation via non-solvent induced phase separation (NIPS) process by immersion precipitation. The effect of concentration of polyethersufone on the formation of cloud point of dope solution in N-methylpirrolidone was investigated.  Two kinds of non-solvent as water and ethanol were used in order to study phase separation mechanism of polymer solution. Base on the amount of non-solvent of water and ethanol needed for cloud point formation, the ternary phase diagram can be performed. The experimental result indicated constant concentration of polyethersulfone, amount of ethanol needed was higher than water to obtain cloud point formation of polymer solution.